Plastidial Glycolytic Glyceraldehyde-3-Phosphate Dehydrogenase Is an Important Determinant in the Carbon and Nitrogen Metabolism of Heterotrophic Cells in Arabidopsis. Issue 3 (1st July 2015) - Anoman, Armand D.; Muñoz-Bertomeu, Jesús; Rosa-Téllez, Sara; Flores-Tornero, María; Serrano, Ramón; Bueso, Eduardo; Fernie, Alisdair R.; Segura, Juan; Ros, Roc
Abstract : A plastidial glycolytic enzyme modulates the metabolism of carbon and nitrogen in nonphotosynthetic cells and affects plant organ development. Abstract: This study functionally characterizes the Arabidopsis ( Arabidopsis thaliana ) plastidial glycolytic isoforms of glyceraldehyde-3-phosphate dehydrogenase (GAPCp) in photosynthetic and heterotrophic cells. We expressed the enzyme in gapcp double mutants ( gapcp1gapcp2 ) under the control of photosynthetic (Rubisco small subunit RBCS2B [ RBCS ]) or heterotrophic (phosphate transporter PHT1.2 [ PHT ]) cell-specific promoters. Expression of GAPCp1 under the control of RBCS in gapcp1gapcp2 had no significant effect on the metabolite profile or growth in the aerial part (AP ). GAPCp1 expression under the control of the PHT promoter clearly affected Arabidopsis development by increasing the number of lateral roots and having a major effect on AP growth and metabolite profile. Our results indicate that GAPCp1 is not functionally important in photosynthetic cells but plays a fundamental role in roots and in heterotrophic cells of the AP . Specifically, GAPCp activity may be required in root meristems and the root cap for normal primary root growth. Transcriptomic and metabolomic analyses indicate that the lack of GAPCp activity affects nitrogen and carbon metabolism as well as mineral nutrition and that glycerate and glutamine are the main metabolites responding to GAPCp activity. Thus, GAPCp could be an important metabolic connector of glycolysis with other pathways, such as the phosphorylated pathway of serine biosynthesis, the ammonium assimilation pathway, or the metabolism of γ-aminobutyrate, which in turn affect plant development.